The Function of Artificial Intelligence for Transcendent Governance with a Strategic Management Approach - Kia Kojouri, Davood (Management Strategies and Engineering Sciences, 2025)
This study follows a qualitative-quantitative method, employing textual content analysis in the qualitative section. Data collection tools include past research documents and library resources in this field. The data analysis method is based on open coding. According to the study’s findings, among 187 relevant articles and books, 42 studies were analyzed using a systematic review. After screening the indicators through the Delphi method, the remaining indicators were categorized into four groups for strengths and weaknesses and three groups for threats and opportunities, resulting in a total extraction of 55 indicators. The statistical population of this research consists of 10 government officials in governance who simultaneously held faculty positions in public administration and had authored works in this domain. In the quantitative section, utilizing the AHP-SWOT approach and analyzing internal and external factor matrices, the study sought to identify the most significant strengths and opportunities. It then developed and prioritized aggressive strategies to provide a practical framework for implementing artificial intelligence in governance. Ultimately, the strategies were ranked using the QSPM method. Based on the research findings, the most significant strength was facilitating informed decision-making based on logic, reason, and intuition, with a weight of 0.057, while the most important opportunity was enhancing democracy, with a weight of 0.105. The strategy of leveraging strengths in informed decision-making to improve democracy was ranked as the top strategy, with a score of 3.234. The results indicated that adopting informed decision-making based on logic and rationality as a superior strategy has significant potential for strengthening democracy and transparency in governance.